Medicinal precautionary measures in the Fiscal Penal Code (Ius Novum, 2022)
The article is a review and is devoted to the issue of therapeutic security measures in the FiscalPenal Code, i.e. therapy, addiction therapy and stay in a psychiatric institution. The measuresin question are fully regulated in the provisions of the Penal Code, in Articles 93b–93g recitedunder Article 20 § 2 of the Fiscal Penal Code on the basis of fiscal penal law. The aboveprovisions concern the general premises and rules of adjudication, subjective adjudicationcriteria, the time of adjudication and the use of therapeutic precautionary measures, and theobligations of the perpetrator against whom therapy, addiction therapy or stay in a psychiatricinstitution was ordered, which corresponds to the structure of the publication. Due to thelack of an autonomous regulation in the provisions of the Fiscal Penal Code with regard tothe discussed safeguards, the problem of the appropriate application of the above-mentionedprovisions of the Criminal Code in fiscal penal law and the actual suitability of therapeuticsafeguards in this branch of law arises. The aim of the article is therefore to analyze articles93b–93g of the Criminal Code and attempt to assess whether the adoption of these provisions on the ground of fiscal penal law has been successful, and to verify the research hypothesisthat therapy, addiction therapy and stay in a psychiatric institution play a significant role infiscal penal law.The subject of the analysis are legal regulations and statements of the doctrine. The articlecontains considerations concerning the normative and dogmatic sphere, and not the sphere ofjudicial application of the law. However, the study is not devoid of references to practice, butis limited only to the statements of the judicature. The research is national in nature. Whenpresenting the topic, the authors used the analysis of legal texts, dogmatic analysis and theanalysis of the Supreme Court and appellate courts. Therefore, the title issue was presentedin a normative, dogmatic and partly practical aspect.
Keywords: therapy; addiction therapy; stay in a psychiatric institution; tax crimes